A New Statistic on Linear and Circular r-Mino Arrangements - Shattuck, Mark A.; Wagner, Carl G. (The Electronic Journal of Combinatorics, 2006)
We introduce a new statistic on linear and circular r-mino arrangements which leads to interesting polynomial generalizations of the r-Fibonacci and r-Lucas sequences. By studying special values of these polynomials, we derive periodicity and parity theorems for this statistic.